PENERAPAN AKAD RAHN TASJILY SEBAGI ALTERNATIF PEMBIAYAAN PADA PRODUK BAROKAH UMKM - M Munim; indah tri kusuma; wahyu Qomariatul Khoiriyah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
In carrying out their activities, UMKM have many obstacles in accessing financing due to a lack of funding. BMT NU Singgahan Bangilan Branch offers a solution to these problems using the Rahn contract, but in its implementation there are problems related to customer negligence in fulfilling its obligations. This study aims to analyze the application of the rahn tasjily contract as an alternative to financing. This research uses a qualitative approach with a case study at BMT NU Singgahan Bangilan Branch. Data was collected through in-depth interviews with management and customers, participatory observations, and document analysis. The HSIL of this project is the application of the rahn tasjily contract on MSME barokah products that have succeeded in minimizing financing risks for BMT and providing easy access for MSME actors to get business capital without losing their assets. Customers are more responsible in paying off financing because the collateral remains in the control of BMT. Kywords: akad rahn tasjiliy, barokah products of UMKM